Retrospective Analyses of Potential Risk Factors for Posterior Capsule Opacification after Cataract Surgery - Shuang Wu; Nianting Tong; Lin Pan; Xiaohui Jiang; Yanan Li; MeiLing Guo; Hehuan Li (Journal of Ophthalmology)
Purpose. To evaluate the potential risk factors of posterior capsule opacification (PCO) after cataract surgery. Methods. Data on PCO patients diagnosed from September 2015 to May 2017 were obtained from the Department of Ophthalmology at Qingdao Municipal Hospital, Qingdao, China. The factors associated with PCO were assessed using Pearson's χ2 test for univariate analyses and logistic regression for multivariate analyses. Results. Eyes (652) from 550 patients were enrolled in this study. All patients were diagnosed with PCO/non-PCO and had <3 years of follow-up after surgery. The numbers of PCO and non-PCO were 108 eyes and 544 eyes, respectively. Statistically significant associations with PCO were found for age at the time of surgery (χ2 = 78.504; p<0.001), diabetes (χ2 = 4.829; p=0.028), immune diseases (χ2 = 4.234; p=0.004), high myopia (χ2 = 5.753; p=0.016), lens nucleus hardness (χ2 = 11.046; p=0.026), surgery type (χ2 = 11.354; p=0.001), a history of vitrectomy (χ2 = 4.212; p=0.004), ocular inflammation (χ2 = 6.01; p=0.009), and the intraocular lens (IOL) type (χ2 = 8.696; p=0.003). Multivariable data analyses using logistic regression analyses of the variables showed that age at the time of surgery <60 years, diabetes, lens nucleus hardness of III–V, extracapsular cataract extraction (ECCE), postvitrectomy, and hydrophilic IOLs were significant independent risk factors associated with PCO. Conclusions. Age <60 years, diabetes, lens nucleus hardness of III–V, ECCE, postvitrectomy, and a hydrophilic IOL were significantly associated with the formation of PCO. Estimation of the incidence of and risk factors for PCO should help in patients counseling and in the design of treatment protocols to reduce or prevent its development.